2008
DOI: 10.1177/0022219408317856
|View full text |Cite
|
Sign up to set email alerts
|

Working Memory Deficits in Children With Specific Learning Disorders

Abstract: This article examines working memory functioning in children with specific developmental disorders of scholastic skills as defined by ICD-10. Ninety-seven second to fourth graders with a minimum IQ of 80 are compared using a 2 x 2 factorial (dyscalculia vs. no dyscalculia; dyslexia vs. no dyslexia) design. An extensive test battery assesses the three subcomponents of working memory described by Baddeley (1986): phonological loop, visual-spatial sketchpad, and central executive. Children with dyscalculia show d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

17
174
4
15

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 191 publications
(211 citation statements)
references
References 45 publications
(75 reference statements)
17
174
4
15
Order By: Relevance
“…The performance on the Corsi Block Tapping test, the Block suppression test, the subtest 'subtraction' of the ZAREKI-R and the digit span forward was significantly lower in children with DD compared to normally achieving controls. These results are in line with findings from other studies (Bull et al, 2008;Schuchardt, Maehler, & Hasselhorn, 2008). Visual-spatial short-term memory span was found to be a predictor specifically of math ability.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The performance on the Corsi Block Tapping test, the Block suppression test, the subtest 'subtraction' of the ZAREKI-R and the digit span forward was significantly lower in children with DD compared to normally achieving controls. These results are in line with findings from other studies (Bull et al, 2008;Schuchardt, Maehler, & Hasselhorn, 2008). Visual-spatial short-term memory span was found to be a predictor specifically of math ability.…”
Section: Discussionsupporting
confidence: 92%
“…Interestingly, in our study there are no differences between groups regarding the digit span backward, which is 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 61 62 63 64 65 predominantly a measure of verbal working memory. Some studies have found impairments in this domain (D'Amico & Guarnera, 2005;Rosselli et al, 2006), whereas others suggest that children with DD do not appear to have a deficit in working memory for language-related tasks (McLean & Hitch, 1999;Schuchardt et al, 2008). Our results may be explained by the small group size of examined children and therefore additional research about the role of verbal working memory in children with DD is required.…”
Section: Discussionmentioning
confidence: 55%
“…In this context, researchers such as Alloway, Gathercole, Willis and Adams (2004) suggest that phonological awareness is not only affected by the tasks of reading and writing, but also by the development of the working memory abilities and by the refinement of other language abilities, in particular vocabulary, which has been confirmed by various studies (Fukuda et al, 2010;Kibby, 2009;Koo, Crain, LaSasso, & Éden, 2008;Schuchardt, Maehler, & Hasselhorn, 2008;Swanson, Zheng, & Jerman, 2009). Oakhill and Kyle (2000) demonstrated associations between the working memory abilities, both storage and processing demands, and two of the phonological awareness abilities (phoneme deletion and sound categorization).…”
mentioning
confidence: 86%
“…However, there is debate on whether this relies on their phonological core deficit or not. For example, Smith‐Spark and Fisk (2007) found that when phonological differences are taken into account, children with dyslexia still show working memory deficits, whereas Schuchardt, Maehler, and Hasselhorn (2008) found that differences between children with and without dyslexia disappear when controlling for phonological differences. Pickering (2012) argued that children with dyslexia have difficulties with the phonological aspects of working memory and the central executive function of working memory.…”
Section: Introductionmentioning
confidence: 99%